Examining the effects of a trauma-informed yoga curriculum on incarcerated individuals - Derlic, Dragana (Criminal justice studies, 2024)
This study explores the effects of a trauma-informed yoga (TIY) curriculum offered by Yoga 4 Change to individuals who were incarcerated. Utilizing data from the Yoga 4 Change organization, we capture the internal changes of individuals participating in a six-week TIY curriculum built on the knowledge of trauma. The data includes measures of individuals’ coping skills, forgiveness, compassion, emotional awareness, emotional regulation, anxiety, anger management, and post-traumatic growth. The data were collected from participants who were randomly assigned to either the experimental or control group for comparison purposes and included pre-test and post-test measures of each scale. The results demonstrate the effectiveness of the six-week TIY curriculum on participants who were incarcerated, showcasing improvements in coping skills and emotional awareness.